In Vitro Antibacterial Activity of Teixobactin Derivatives on Clinically Relevant Bacterial Isolates - Ramchuran, Estelle J.; Somboro, Anou M.; Abdel Monaim, Shimaa A. H.; Amoako, Daniel G.; Parboosing, Raveen; Kumalo, Hezekiel M.; Agrawal, Nikhil; Albericio, Fernando; Torre, Beatriz G. de La; Bester, Linda A. (Frontiers in Microbiology, 2018)
Methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant enterococcus (VRE) are included on the WHO high priority list of pathogens that require urgent invention. Hence emphasis needs to be placed on developing novel class of molecules to tackle these pathogens. Teixobactin is a new class of antibiotic that has demonstrated antimicrobial activity against common bacteria. Here we examined the antimicrobial properties of three Teixobactin derivatives against clinically relevant bacterial isolates taken from South African patients. The minimum inhibitory concentration (MIC), the minimal bactericidal concentration (MBC), the effect of serum on MICs and the time-kill kinetics studies of our synthesized Teixobactin derivatives (3, 4 and 5) were ascertained following the CLSI 2017 guidelines and using the broth microdilution method. Haemolysis on red blood cells (RBCs) and cytotoxicity on peripheral blood mononuclear cells (PBMCs) were performed to determine the safety of these compounds. The MICs of 3, 4 and 5 against reference strains were 4–64 µg/ml, 2–64 µg/ml and 0.5–64 µg/ml, respectively. The MICs observed for MRSA were (3) 32 µg/ml, (4) 2–4 µg/ml and (5) 2–4 µg/ml whilst those for VRE they were (3) 8–16 μg/ml, (4) 4 μg/ml and (5) 2–16μg/ml, respectively. In the presence of 50% human serum, there was no significant effect on the MICs. The compounds did not exhibit any effect on cell viability at their effective concentration. Teixobactin derivatives (3, 4 and 5) inhibited bacterial growth in drug-resistant bacteria and hence emerge as potential antimicrobial agents. Molecular dynamic simulations suggested that the most dominant binding mode of Lys10-teixobactin (4) to lipid II is through the amide protons of the cycle, which is identical to data described in the literature for the natural teixobactin hence predicting the possibility of a similar mechanism of action.